Pengaruh Operating Cash Flow dan Financial Distress terhadap Penerimaan Opini Audit Going Concern - Herdiansyah, Aditia; Novayanti, Deasy (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2025)
This study aims to analyze the influence of Operating Cash Flow and Financial Distress on the going concern audit opinion of manufacturing sector companies listed on the Indonesia Stock Exchange (IDX) during the period 2020 to 2022. A going concern audit opinion is an auditor’s statement regarding a company’s ability to continue its operations, serving as a crucial indicator for stakeholders in making economic decisions. Therefore, a deeper understanding of the factors that influence auditors in issuing such opinions is essential. This research adopts a quantitative approach using panel data logistic regression analysis. The analytical model employed is the Fixed Effect Model (FEM), selected based on the results of the Chow and Hausman tests. The study sample consists of 23 manufacturing companies selected purposively according to specific criteria. The results indicate that the Operating Cash Flow variable has a significant effect on the going concern audit opinion, as evidenced by a significance value of 0.0003. This implies that the lower a company’s operating cash flow, the higher the likelihood of receiving a going concern opinion from the auditor. Similarly, the Financial Distress variable also has a significant influence, with a significance value of 0.0057, indicating that high financial pressure (as reflected by a lower Z-score) correlates with an increased risk of receiving a going concern opinion. Simultaneously, both variables have a significant effect on audit opinion, as shown by the F-test probability value of 0.000800 and an R-squared value of 0.3485. These findings suggest that auditors consider key internal financial factors when evaluating a client’s going concern risk.